The organisational context of nursing practice in hospitals in China and its relationship with quality of care, and patient and nurse outcomes: A mixed‐methods review. Issue 1 (24th September 2020) - Ying, Liying; Fitzpatrick, Joanne M.; Philippou, Julia; Huang, Wenjie; Rafferty, Anne Marie
Abstract: Background: Achieving high‐quality care and retention of nurses are major concerns for nurse leaders in hospitals. The organisational context is theorised to influence the quality of care and patient and nurse outcomes. This review focuses on China where the healthcare system is different from most Western countries in terms of government healthcare expenditure, public health insurance and healthcare delivery system. Objectives: To explore the organisational context of nursing practice in hospitals in China and its relationship with quality of care, patient outcomes (patient adverse events, safety and satisfaction) and nurse outcomes (burnout, job satisfaction and intention to leave). Design: A mixed‐methods review. Data sources: The electronic databases PubMed, EMBASE, CINAHL, PsycINFO and China Academic Journals Database were used. Methods: This review was conducted using the SALSA (Search, Appraisal, Synthesis and Analysis) framework. Quality assessment was conducted using the Joanna Briggs Institute (JBI) critical appraisal checklists for cross‐sectional studies and qualitative research. A narrative synthesis was conducted and was supported by tabulation of study data. The PRISMA guidelines were used for this review. Results: Twenty‐three articles met the inclusion criteria and were retrieved, analysed and synthesised. This review supports the link between organisational context, quality of care, and patient and nurse outcomes in the Chinese healthcare system. Aspects of organisational context warrant attention including nurse staffing levels, the shortage of nurses, a lack of nurse participation in hospital affairs and support for the professional development of nurses. Conclusions: The findings suggest that tailored interventions are needed to improve the organisational context of nursing practice in Chinese hospitals and, in particular, to address the nurse workforce issues and organisational leadership and support. The unique policy context of the Chinese healthcare system should be considered when developing these interventions. Relevance to Clinical Practice: Recognising the im p ortance of the organisational context, it is imperative that nurse leaders make every effort to legislate for safe nurse staffing and to establish a caring culture to improve quality of care and nurse and patient outcomes.